A longitudinal examination of students' health behaviours during their first year at university. Issue 1 (2nd January 2018) - Gibson, Ann-Marie; Shaw, Johanna; Hewitt, Allan; Easton, Chris; Robertson, Sarah; Gibson, Neil
Abstract: During the transition from school to higher education, young adults experience a substantial amount of change where they progress from the highly controlled setting of school to the autonomous and self-motivated environment of university. Time spent at university is considered a critical period during which young adults establish a clear sense of identity, which can include forming positive health behaviours such as regular physical activity. The transition from school to university also involves a number of changes that can impact on the mental well-being of students including financial concerns, academic pressures and a lack of social support. Our aim was to longitudinally examine the physical activity levels and mental well-being of Scottish students during their first year at university. Participants were 48 first-year students (males, n  = 24; females, n  = 24) aged 18–19 years enrolled at two Scottish universities in the UK. At entry to university (semester 1) participants completed a validated self-report measure of physical activity and measures of anxiety and depression. Participants' physical activity levels were assessed for seven days via accelerometry. Participants completed the same measures six months later (semester 2). Daily moderate physical activity levels decreased across the semesters yet perceptions of mental well-being remained stable. There was a significant increase in hip and waist circumferences across the semesters. The first year of university is a critical period for establishing positive health behaviours and there is a need for universities to actively encourage physical activity as an integral part of university life.